Monetary policy and bank profitability in a low interest rate environment - Carlo Altavilla; Miguel Boucinha; José-Luis Peydró (Economic Policy, 2018)
We analyse the impact of standard and non-standard monetary policy on bank profitability. We use both proprietary and commercial data on individual euro area bank balance-sheets and market prices. Our results show that a monetary policy easing – a decrease in short-term interest rates and/or a flattening of the yield curve – is not associated with lower bank profits once we control for the endogeneity of the policy measures to expected macroeconomic and financial conditions. Accommodative monetary conditions asymmetrically affect the main components of bank profitability, with a positive impact on loan loss provisions and non-interest income offsetting the negative one on net interest income. A protracted period of low monetary rates has a negative effect on profits that, however, only materialises after a long time period and is counterbalanced by improved macroeconomic conditions. Monetary policy easing surprises during the low interest rate period improve bank stock prices and CDS.
Keywords: E52; G01; G21; G28; E43; 330; bank profitability; monetary policy; lower bound; quantitative easing; negative rates